Twittering on about mental health: is it worth the effort? - Jayaram, Mahesh; Moran, Lindsay; Adams, Clive E. (BMJ Publishing Group, 2017)
The medical community disseminates information increasingly using social media. Randomised controlled trials are being conducted in this area to evaluate effectiveness of social media with mixed results so far, but more trials are likely to be published in the coming years. One recent twitter randomised control trial using Cochrane Schizophrenia Group reviews suggests that tweets increase the hits to the target web page by about threefold and time spent on the web page is also increased threefold when referrals come in via twitter. These are early findings and need further replication. Twitter appeals to professionals, entertainers and politicians among others as a means of networking with peers and connecting with the wider public. Twitter, in particular, seems to be well placed for use by the medical community and is effective in promoting messages, updating information, interacting with each other locally and internationally and more so during conferences. Twitter is also increasingly used to disseminate evidence in addition to traditional media such as academic peer-reviewed journals. Caution is required using twitter as inadvertent tweets can lead to censure. Overall, the use of twitter responsibly by the medical community will increase visibility of research findings and ensure up to date evidence is readily accessible. This should open the door for further trials of different social media platforms to evaluate their effectiveness in disseminating accurate high-quality information instantaneously to a global audience.